THE EFFECT OF COOPERATIVE LEARNING MODEL OF NUMBER HEAD TOGETHER (NHT) TYPE ASSISTED ANIMATION ON STUDENT’S LEARNING OUTCOMES OF X CLASS SMA 2 LINTONGNIHUTA A.Y. 2014/2015 - Nancy Alretni Mendrofa; Jonny H. Panggabean (INPAFI (Inovasi Pembelajaran Fisika), 2016)
ABSTRACT Aims of study to determine the effect of cooperative learning model of NHT type to learning outcomes of students in  subject matter  optical geometry in high school N 2 Lintongnihuta A.Y. 2014/2015.Kind of this research is quasi experimental. The population in this research were all students of class X Semester II SMA N 2 Lintongnihuta which consists of two classes. Sampling was done by purposive research by using two existing classes, namely class X Mia 2 were 26students as experimental class and the class X Mia 1 amounted to 30 students as the control class. The instrument used is a cognitive test in the form of multiple choice question number 20 and observation sheet of student’s activity. Experimental class was given treatment by cooperative learning model of  NHT type and grade control with conventional learning. Before being given different treatment performed pretest, which is the average value of the experimental class pretest 48.65 with a standard deviation  11.45 and the average value of the control class pretest 48.67 with a standard deviation 14.07. Second class pretest data testing showed that both classes of data were normally distributed and homogeneous. The test results obtained pretest tcount<ttable (0.0057 <2,14) then H0 is received, it means the ability of students' initial experimental class and control class alike. Then given treatment that is experimental class with cooperative learning model of NHT type and grade control with conventional learning models. During thelearning processinthe experimental classlearning activities of studentsincreased, the meetingI59.79%, 72.07%meetingIIandIIImeeting of75.30%.After the study was completed, given postest with an average 66.53 for experimental class with a standard deviation 11.64 and 48.66 with the control class standard deviation 14.07. On testing normality and homogeneity of data obtained postest that both classes of data were normally distributed and homogeneous. The data processing postest obtained that tcount= 5.1 and ttable = 2.14, so that t count > t table (5.1> 2.14) then Hareceived means there is influence of cooperative learning model of NHT type to students learning outcomes  in optic geometry material to X class SMA N 2 Lintongnihuta A.Y. 2014/2015. Keywords: Cooperative learning model of NHT type , animation, learning outcome, activity.